(untitled) (Journal of responsible AI & ethics, 2026)
The rapid development of Artificial Intelligence (AI) has introduced groundbreaking advancements in various fields, but it has also raised significant ethical challenges. The integration of AI into decision-making processes, healthcare, law enforcement, finance, and daily life presents both vast opportunities and potential risks. As AI systems become more capable, it is essential to understand the ethical boundaries that must guide their development and deployment. This paper explores the complex ethical dilemmas associated with AI, focusing on issues such as bias, transparency, accountability, privacy, and the impact on employment. It examines the responsible use of AI and the fine line between harnessing AI’s potential and ensuring that it does not perpetuate harm or reinforce societal inequalities. Through a review of ethical frameworks, case studies, and empirical research, this paper provides insights into how AI can be developed and utilized in a manner that respects human rights and societal values. The findings highlight the need for robust ethical guidelines, regulatory frameworks, and multi-stakeholder collaboration to ensure that AI serves the public good while minimizing risks.